Expenditure rules: Limiting the level or the variation of public expenditure? - Séverine Menguy (Economies, 2024)
The main goal of the first-generation expenditure rules was to ensure fiscal discipline: preserving a sound fiscal framework and public debt sustainability. Regarding this goal, analytically as well as empirically, limiting the share of public expenditure in GDP would be more appropriate in case of weak potential economic growth or if the public expenditure-to-GDP ratio is high. On the contrary, limiting the variation of public expenditure would be more appropriate for countries with high potential economic growth or with a weak public expenditure-to-GDP ratio. The second goal of expenditure rules is to contribute to sustaining economic activity. Regarding this goal, limiting the level of public expenditure appears as more favorable than limiting the variation of public expenditure. Indeed, a rule in terms of variation could hamper economic growth, especially for countries with a high public expenditure-to-GDP ratio.
Keywords: 330; fiscal rules; expenditure rules; public expenditure; fiscal discipline; economic activity